2005
DOI: 10.1007/s00383-005-1580-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diclofenac on germ cell apoptosis following testicular ischemia-reperfusion injury in a rat

Abstract: Recent evidence suggests that enhanced cell apoptosis is responsible for germ cell loss following testicular ischemia-reperfusion (IR) injury. A nonsteroidal anti-inflammatory drug diclofenac sodium (Voltaren) is a prostaglandin-synthesis inhibitor, which is widely used in many testicular disorders. The purpose of the present study was to examine the effect of diclofenac (DIC) on germ cell apoptosis in the ischemic and contralateral testes following testicular IR in a rat. Forty rats were divided randomly into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 25 publications
0
51
0
6
Order By: Relevance
“…Failure of metabolic supply, owing to the dimunition of oxygen in ischemia, decreased cellular stores, and accumulation of toxic metabolites lead to germ cell death. 1 Rotation of spermatic cord is initially accompanied by edema attributed to venous and lymphatic obstructions. Advancement of obstruction impedes arterial circulation, which is followed by testicular infarct.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure of metabolic supply, owing to the dimunition of oxygen in ischemia, decreased cellular stores, and accumulation of toxic metabolites lead to germ cell death. 1 Rotation of spermatic cord is initially accompanied by edema attributed to venous and lymphatic obstructions. Advancement of obstruction impedes arterial circulation, which is followed by testicular infarct.…”
Section: Introductionmentioning
confidence: 99%
“…3 Free-oxygen radicals are linked with ischemia reperfusion (I/R) injury. 1 These free-oxygen radicals exert their deleterious effects by destruction of the structural elements of the cell. Various antioxidants, like vitamin E, allopurinol, and melatonin, have been used to alleviate the hazardous impacts of free-oxygen radicals.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Therefore, many pharmaceutical agents are under investigation that can be used as an adjunct to surgery in order to improve the testicular salvage rates. [3][4][5][6][7][8] Montelukast is a selective antagonist of cysteinyl leukotriene receptor 1 (CystLT1) and an anti-oxidant used as an anti-asthmatic drug in the clinical setting. It has been previously reported in experimental studies that it preserves the kidney and the bladder from ischemia/reperfusion damage.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of fertility loss following testicular torsion depends on the extent of the ischemia and the subsequent damage to the contralateral testis. Substantial body of growing evidence has suggested that testicular ischemia impairs the blood-testis barrier and exposes the contralateral testis to the potential risk of autoimmunization against its own spermatogenic cells [9].…”
Section: Short Communicationmentioning
confidence: 99%
“…Based on this concept, several pharmacological agents as well as surgical interventions have been examined to prevent or reverse ischemia-reperfusion induced fertility problems [5][6][7][8][9][10][11][12].…”
Section: Short Communicationmentioning
confidence: 99%